Glycated Collagen Stimulates Differentiation of Gingival Myofibroblasts. Issue 9 (1st September 2017) - Retamal, Ignacio N.; Hernández, Romina; Melo, Francisco; Zapata, Paulina; Martínez, Constanza; Martínez, Jorge; Smith, Patricio C.
Abstract : Background: Glucose‐derived metabolites may alter the structure and biologic properties of important proteins in periodontium, such as collagens. As a consequence, it is possible that collagen‐binding cells may change their phenotypic traits. Although the glucose‐derived product methylglyoxal (MGO) has been detected in periodontal lesions, the precise effect of collagen glycation on gingival connective tissue biology is not fully understood. The present study evaluates whether collagen glycation by MGO may affect phenotypic properties and remodeling capacity of human gingival fibroblasts (HGFs). Methods: Primary cultures of HGFs were grown on Type I collagen matrices previously treated with MGO. Cell cultures were tested for cell viability, apoptosis, α‐smooth muscle actin (SMA), fibronectin (FN) production, and collagen remodeling. Mechanical properties and morphology of MGO‐treated collagen gels were evaluated using rheometry and atomic force microscopy. Statistical analysis was performed by Kruskal‐Wallis and Mann‐Whitney U tests. Results: MGO‐treated collagen did not affect cell viability or apoptosis. In addition, MGO did not induce significant changes in morphology or mechanical properties of the collagen matrix. However, MGO‐treated collagen stimulated an increase in the myofibroblast marker α‐SMA, production and assembly of FN, and contraction of collagen matrices. Moreover, use of a triple‐helical peptide that reconstitutes the collagen‐binding domain for integrins GFOGER reverted the assembly of FN induced by MGO‐treated collagen. Conclusions: The present study shows that collagen glycation by MGO stimulates differentiation of myofibroblasts and production and assembly of FN. These responses may alter the homeostatic balance and wound‐healing response of gingival connective tissues affected by diabetes mellitus or aging.